Corneal epithelial thickness and corneal curvature changes during the day: The effects of daily disposable contact lens wear - TOKER, AYŞE EBRU; AKKAYA TURHAN, SEMRA (ELSEVIER, 2020)
Purpose: To evaluate the changes in corneal epithelial thickness and corneal anterior and posterior curvatures during the day, and the effect of wearing daily disposable soft contact lenses. Methods: Thirty-two healthy volunteers were enrolled in a randomized crossover study. At the baseline visit, corneal and epithelial thickness maps (OCT; Optovue, Inc., Fremont, CA, USA) and keratometric measurements (Pentacam, Oculus, GmbH, Germany) were performed in the morning and in the afternoon (8 hours after). Then, each subject was fitted with the following brands of daily disposable contact lenses in random order: Dailies Total 1 (Delefilcon A), Dailies Aqua Comfort (Nelfilcon A), TruEye (Narafilcon A) and Biotrue Oneday (Nesofilcon A) on different days. All fitted lenses had a power of -3.00 diopters (D). Measurements were repeated before putting the contact lens on and after an -eight -hour contact lens wear. Results: With no lens wear, the anterior topographic indices showed significant steepening [Kflat: p < 0.0001; Ksteep: p 0.0001 and maximum keratometry value (Kmax): p = 0.04] and the corneal thickness significantly decreased in the central and temporal portion of the cornea in the afternoon. There were no significant changes in the posterior topographical indices and corneal epithelial thickness. With contact lens wear, no significant change occurred in the corneal and epithelial thickness, and the anterior and posterior curvatures during the day (all p values 0.05). There was no statistically significant difference in the epithelial thickness among the groups wearing different contact lens types (p > 0.05). Conclusions: Anterior corneal topographic indices steepen depending on the natural diurnal variations. Daily wear of soft contact lenses appears to mask this steepening. The corneal epithelial thickness is not affected by daily disposable soft contact lenses.
Keywords: Corneal epithelial thickness; Corneal curvatures; Daily disposable contact lenses; LONG-TERM WEAR; DIURNAL-VARIATION; EXTENDED WEAR; IN-VIVO; OXYGEN TRANSMISSIBILITY; COMFORT; SHAPE